2020
DOI: 10.1186/s13102-020-00168-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular shoulder activity during exercises with different combinations of stable and unstable weight mass

Abstract: Background: Recent shoulder injury prevention programs have utilized resistance exercises combined with different forms of instability, with the goal of eliciting functional adaptations and thereby reducing the risk of injury. However, it is still unknown how an unstable weight mass (UWM) affects the muscular activity of the shoulder stabilizers. Aim of the study was to assess neuromuscular activity of dynamic shoulder stabilizers under four conditions of stable and UWM during three shoulder exercises. It was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…1,9 There are other studies that have obtained similar results to ours in other regions of the body. Baritello et al 46 found that training with an unstable weight mass elicited higher muscle activity in the shoulder muscles when compared with a weight with stable mass behavior. Lawrence et al 47 observed that suspending barbell weights with elastic bands can increase trunk stabilizing muscle activity more than free weights.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 There are other studies that have obtained similar results to ours in other regions of the body. Baritello et al 46 found that training with an unstable weight mass elicited higher muscle activity in the shoulder muscles when compared with a weight with stable mass behavior. Lawrence et al 47 observed that suspending barbell weights with elastic bands can increase trunk stabilizing muscle activity more than free weights.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic athletes present a reduction in the lower trapezius activity and an increase in the upper trapezius activity. and the increase in load tends to increase the intensity of the muscular activity [ 24 , 42 , 52 ]. Athletes whose sport involves aerial movements showed higher muscle strength compared to athletes from other sports [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sports training, it is necessary to consider the effectiveness of skeletal muscle activity and assess body response in relation to pre-established exercise, observing strength, endurance, and muscle activity [22,23]. Therefore, it is justi able to evaluate the electromyographic behavior of the masseter and temporalis muscles of participants who practice CrossFit exercise to understand whether there is a relationship between high-intensity sports and the functionality of the dynamic structures of the stomatognathic system.…”
Section: Discussionmentioning
confidence: 99%